Kepemimpinan Transformasional dan Adaptif dalam Kelembagaan PAI untuk Menghadapi Tantangan Perubahan pada Lembaga Pendidikan Tingkat Dasar - Moh. Nasrul Amin; Rahmad Hariyadi (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2026)
This study aims to conduct an in-depth and systematic examination of the integration between transformational leadership and adaptive leadership within the institutional context of Islamic Religious Education (IRE) at the elementary level. The study employs a qualitative approach using a literature review method, analyzing relevant scientific literature, including leadership theories, educational policies, and previous research findings. The findings indicate that transformational leadership plays a crucial role in establishing vision, inspiration, and a values-based culture within the IRE institutional framework, while adaptive leadership is necessary for navigating social change, addressing undefined challenges, and fostering institutional flexibility. The integration of the two models produces a strategic and responsive leadership pattern that not only drives innovation but also strengthens organizational resilience in facing the dynamics of modern education. The implication is that this transformational-adaptive leadership model can be a strategic alternative in strengthening the governance of PAI institutions and serve as a reference for the development of policies and training in Islamic educational leadership oriented toward sustainability and institutional quality.